Structural and magnetic properties of nanocrystalline Bi1-xLaxFeO3 (0.0 ≤ x ≤ 0.4) synthesized by a mechanochemical route - Cristobal, Adrian Alberto (2017)
Bi1-xLaxFeO3 (0.0 ≤ x ≤ 0.4) powders were prepared by means of a solid acid-base reaction induced by mechanochemical energy. Bi, La and Fe chlorides were high-energy ball-milled with NaOH, yielding a mixture of Bi1-xLaxFeO3 and NaCl. After heating and washing, nanoparticles of Bi1-xLaxFeO3 were obtained as a main product, with low contents of secondary phases. Structural characterization was performed by X-ray diffraction (Rietveld refinement) and Raman spectroscopy. The hyperfine magnetic behavior was analyzed by means of Mössbauer spectroscopy and the microstructure of the particles was evaluated by transmission electron microscopy. Differential scanning calorimetry was employed to investigate the thermal behavior of the samples and magnetic measurements at room temperature were also carried out. Crystal structure transitions as a function of composition were identified. Moreover, an intricate magnetic behavior was observed, which was explained on the basis of the concomitant contribution of two different canting levels of the antiparallel spins.